THE IMPORTANCE OF INVESTMENTS IN ENSURING THE ECONOMIC SECURITY OF THE COUNTRY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article, the issues of attracting investments to the economy of our country and their role in the field of foreign trade, as well as the economic essence of investments and foreign economic activity, an important factor in ensuring sustainable economic growth and state management in the implementation of its active investment policy, including Information about investment processes in the economy of Uzbekistan is provided.